(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: as of January 2020, when the WHO declared the SARS-CoV-2 COVID-19 infection as a global health emergency, action protocols and activities began to be implemented in pediatric care centers with the purpose preparing and containing the pandemic. Objective: describe the results of hospital surveillance and the epidemiological-clinical characteristics of children and adolescents with a SARS-CoV-2 COVID-19 infection between 4/1/2020 and 4/30/2021 in a pediatric hospital. Material and methods: a retrospective descriptive observational study was carried out. Period: 4/1/2020-4/30/2021. All children and adolescents under 16 years of age with diagnosis of SARS-CoV-2 COVID-19 infection by PCR test and assisted by the In-Hospital Infectious Diseases Center (CIH) and by the Pediatric Epidemiology and Infectiology Unit. A PCR test for SARS-CoV-2 was performed to all hospitalized users and to those included in SARI surveillance as defined for this case, and to children and adolescents with prolonged hospitalizations every 10 days. Data source: active surveillance established by the CIH, medical records, laboratory data. Variables: sex, age, reason for testing, comorbidities, contact, clinical presentation, evolution, hospital outbreaks. Statistical Analysis: frequency distribution and summary measures. Ethical considerations: anonymity throughout the analysis and communication process. Results: in the period analyzed, 10,645 PCR tests were performed. 53 cases were identified as positive, 7 (13.2%) were in 2020 (November and December), 46 (86.8%) in 2021 (January to April), 30 (56.6%) were female. Age: 23 (43.4%) were under 1 year of age. Median 2.5 years. 13 patients had comorbidities (24.5%). In 30 cases (56.6%), the reason for the test was the presence of compatible symptoms, while 22 (41.5%) were asymptomatic. In 40 cases (75%), we identified a home contact as a source of contagion. 39 cases remained hospitalized, 5 required ICU. 14 cases were assisted on an outpatient basis. None died. A single case was caused by an outbreak of nosocomial transmission involving three users in this period, which was controlled timely. No infections were recorded from users to health staff in the period analyzed. Conclusions: hospital surveillance and control strategies have enabled us to identify cases of COVID-19 in a timely manner and control transmission. Cases grew exponentially in line with the national epidemiological situation in the period analyzed.